Ерөнхий суурийн физикийн хичээлийн виртуал загвар бүтээж сургалтад ашиглах нь - Bayarsaikhan, Altankhuu; Мөнхжаргал; Дөлгөөн (Scientific transaction of the National University of Mongolia. Physics, 2022)
A brief report on computer simulations and virtual physical models created and used as part of general education courses in physics, taught by some lecturers at our department during the academic year of 2020-2021, is given. A "light" comparative analysis of the models and exemplary models was carried out. The reference models are from the PhET Interactive Simulations for Science and Math project, developed by a team from the University of Colorado at Boulder, USA. The simulation software is the web-based GlowScript (Web VPython) language. The simulations were developed, run, and tested on Intel i7 Quad-Core CPU, 2.3 GHz, 16 Gb RAM. Keywords: learning technology, learning materials, general physics, physics training, computer modeling, science, information technology, virtual design, simulation, GlowScript, Python, VPython.